The effects of work-family experiences on health among older workers - Cho, Eunae (2020)
With the rapidly aging workforce worldwide, the need to retain healthy older workers is greater than ever. To promote health among older workers, a better understanding of the factors that contribute to their health is crucial. With this in mind, we investigated the impact of work-family conflict and work-family enrichment on older workers' health. Five waves of longitudinal data from the Health and Retirement Study were used. A total of 4,509 workers aged 55 years and older at baseline were included. Multilevel modeling was conducted to analyze the data. Our findings showed that greater work-to-family conflict was related to higher comorbidity and greater disability over time, controlling for other known predictors of health (employment status, total household income, living arrangement, marital status, depressive symptoms, and baseline demographic characteristics). No other work-family variables significantly predicted the health outcomes. Comorbidity and disability were also found to predict work-to-family conflict. Using five waves of longitudinal data, our research showed that work that interferes with family negatively affects older workers' physical and functional health and that health relates to work-to-family conflict. Given the growing number of older workers and changing work and family situations, continued monitoring of work-family experiences among older workers is warranted.